Factors Affecting Brand Trust: An Exploratory Investigation Among Indian Retail Consumers - Panda, Rajesh; Swar, Biranchi Narayan; Mukerjee, Kaushik (Indian Journal of Marketing, 2014)
Retailers aim at building brands that can command loyalty and win the trust of consumers. The valuations of brands undertaken by Interbrand shows that brands like Coca-Cola, Microsoft, Wal-Mart, and so forth are valued at sums larger than their turnovers. However, all brands do not succeed in becoming highly valued brands. When it comes to succeeding with branding, one of the key aspects of branding has been winning the 'trust' of consumers. This paper sets out to focus on the various aspects that engender brand trust among consumers of organized retail stores in India through a survey of consumers and elucidates the factors retailers need to manage to enable brand trust. We collected data from 260 shoppers by using 16 variables. The collected data were subjected to exploratory factor analysis (EFA) with principal axis factoring. The findings indicate that the retail consumer brand trust in India is influenced by four factors - Customer Commitment, Reliability, Reputation, and Retail Environment. The managerial implications of the present study are that retailers need to adopt strategies that evince customer commitment and a very good shopping ambience if they wish to engender brand trust and create a large base of loyal customers.